The impact of CEO educational background on corporate risk-taking in China - Jinyi Zhang; Chunxiao Xue; Jianing Zhang (Journal of Risk and Financial Management, 2023)
This article investigates whether, and how, CEO educational background affects Chinese corporate risk-taking. Using a sample of 4681 firm-year observations from 2012 to 2020, we find that CEO educational background is negatively associated with corporate risk-taking. The nonlinear quadratic regression shows a convex relationship, consistent with the finding that the effect is more profound for the subsample with relatively lower education levels. The negative relationship is stronger for the firms with higher leverage, with lower tangibility, and in non-manufacturing industries. We also address the endogeneity issue using a two-stage least squares regression. This paper may provide valuable insights for shareholders, helping them to hire the most suitable CEOs to achieve shareholders' objectives and increase the corporation's competitiveness in the market.
Keywords: G11; G24; G32; 650; CEO; Chinese stock market; educational background; risk taking